Biodiversity and environment : proceedings of the National Seminar on Environmental Biology, April 3-5, 1998 - Aditya, A. K.; Haldar, P. (Delhi : Daya Pub. House, 2000)
In the Indian context.
Includes bibliographical references.
Keywords: Biodiversity -- India; Biodiversity conservation -- India